Parameters Associated With Mandibular Osteoradionecrosis. (December 2018) - Mendenhall, William M.; Suárez, Carlos; Genden, Eric M.; de Bree, Remco; Strojan, Primož; Langendijk, Johannes A.; Mäkitie, Antti A.; Smee, Robert; Eisbruch, Avraham; Lee, Anne W.M.; Rinaldo, Alessandra; Ferlito, Alfio
Abstract : The objective of this review is to discuss factors related to the risk of osteoradionecrosis (ORN) and how to minimize the likelihood of this complication. A PubMed search for publications pertaining to ORN within the last 3 years was conducted revealing 44 publications. The bibliographies of these publications were reviewed to identify additional references spanning a longer time period. The incidence of ORN is 5% to 10% with a median latency period of 1 to 2 years or less. The likelihood of ORN depends on a number of factors including primary site and extent of disease, dental status, treatment modality, radiotherapy (RT) dose, volume of mandible included in the planning target volume, RT fractionation schedule and technique, and teeth extractions. The risk of ORN may be reduced by limiting the RT dose and volume of mandible irradiated without increasing the risk of a local-regional recurrence due to a marginal miss.